Third new fossil species of the genus Ephedrus Haliday, 1833 (Hymenoptera: Braconidae: Aphidiinae) from Baltic amber - Davidian, Elena M.; Manukyan, Andranik R.; Belokobylskij, Sergey A. (Zootaxa, 2023)
A new species of aphid parasitoid from the genus Ephedrus Haliday, E. zaikai Davidian, sp. nov. (Braconidae: Aphidiinae), is described and illustrated from Late Eocene Baltic amber. This new species was compared with described fossil taxa Ephedrus mirabilis Timon-David, 1944 (Oligocene imprint from Bassin de Marseille), Ephedrus carsteni Davidian, 2023 and E. primordialis Brues, 1933 (both from Eocene Baltic amber), and E. rasnitsyni Davidian & Kaliuzhna, 2021 (Eocene Sakhalinian amber), as well as with extant E. niger Gautier, Bonnamour & Gaumont, 1929 and E. chaitophori Gӓrdenfors, 1986.